Assess social media threats to keep your students and campus safe. Issue 6 (19th September 2016) - Sutton, Halley
Abstract : PHOENIX — Your most effective tool for monitoring the behavior and potential threats from students or toward students on campus comes not from your on‐campus cameras but from the social media traffic generated by your students. According to a report by Common Sense Media, students visit social media sites on average 100 times per day. With the amount of traffic generated by those sites, your institution can't possibly catch all potential threats or incriminating posts.